Development of airglow oh temperature imager for mesopheric study - Bageston,José Valentin; Gobbi,Delano; Takahashi,Hisao; Wrasse,Cristiano Max (Sociedade Brasileira de Geofísica, 2007)
In this work we present a methodology to calculate the temperature in the upper mesosphere using a spectral OH (6-2) airglow temperature imager. The temperature imager system consists of a CCD camera and an optical head (including an interferometer filter, Fresnel lens and objective lens) which was developed by Airglow group of INPE in São José dos Campos, Brazil. The instrument calibration was performed at National Institute of Polar Research, Japan, using a 2 m diameter integrating sphere. The airglow test observations were carried out at Cachoeira Paulista Observatory (22.7ºS), Brazil, from March to May 2005, and the results were compared to that obtained by a tilting-filter zenith photometer (MC2) at the same place. Some results are presented and compared with MSISE-90 atmospheric temperature model, which showed a good agreement in the nocturnal mean values, while exhibiting a different nocturnal variability.